Comprehensive Review of the Elbow Physical Examination. Issue 19 (1st October 2018) - Smith, Matthew V.; Lamplot, Joseph D.; Wright, Rick W.; Brophy, Robert H.
Abstract : Physical examination of the elbow is a critical component in formulating an accurate diagnosis. Various special physical examinations have been described to improve the clinician's ability to establish an accurate diagnosis. A comprehensive approach to the physical examination of the elbow, including special tests, may facilitate improved diagnosis of elbow pathology.